Association between malaria parasite density and hematological profile in malaria infected children at a Nigerian Private hospital - Oyedeji Olusola Adetunji (Journal of Vector Borne Diseases, 2024)
Background & objectives: The correct association between Plasmodium falciparum parasite density and the cellular constituents of blood is not known in entirety in Nigerian children. Thus, we decided to study the association between cellular blood constituents and malaria parasite density in malaria infected children attending a Nigerian hospital. Methods: A study of all children diagnosed with malaria fever at the Pediatric out-patient clinic, Cedar Crest Hospital, Abuja, Nigeria, was conducted. Packed cell volume, white blood cells with differentials and platelet counts and malaria parasite densities obtained from blood samples were studied. Malaria parasite densities more than 2 pluses were classified as significant parasitemia and 1 plus as non-significant. Information obtained was recorded and analysed with SPSS 22 software. Results: A total 143 children (74 boys and 69 girls) diagnosed with malaria of ages between 5 months to 17 years (mean 5.24 ±4.60) were studied. The majority of 141 (98.6%) had non-significant P. falciparum parasitemia, while 2 (2.4%) had significant parasitemia. Of the 143 children with malaria, 116 (81.1%) had a normal leucocyte count. All children with significant parasitemia had a normal leucocyte count. Of the 143 children, 11 (7.7%) had anemia and 10 (7.0%) thrombocytopenia. Anemia, monocytosis and thrombocytopenia were significantly associated with significant malaria parasitemia (p<0.05). Mean platelet counts was significantly less amongst those with significant parasitemia (p<0.01). Interpretation & conclusion: All patients with significant malaria parasitemia had normal leucocyte count. Significant malaria parasitemia is significantly associated with anemia, thrombocytopenia and monocytosis. Blood film appearances showing these changes are suggestive of significant malaria parasitemia.